Wzorzec gatunkowy tekstowych instrukcji użytkowania w perspektywie diachronicznej - Troszczyńska-Nakonieczna, Wiesława (Stylistyka, 2021)
The article deals with the analysis for the use’s instruction as a speech genre in the chronological perspective sińce the 60’s in twentieth century until the beginning of the twenty First century. The author presents a brief outline history of the instruction’s forma- tion in a written form and the transformation of the genre model, with a special emphasis on: the structural level (composition, shape and segmentation of the text), the cognitive level (the way of presenting specific technical information), the pragmatic level (the dominant intents, the sender’s attitude), and stylistic one (text shematisms, formula, assecu- ration). The instruction for use in the chronological prospect characterizes dynamism of change. Integrating in their own structure of other pattems (an advice, a cooking recipe, an advertisement), they took over a book form. Despite of recommendation of European Union’s directive conceming its preparation, it is still realizing variants of genre model: altemation and adaption models. That makes us classify it as a separate genre evolving in accordance with the culture’s development rhythm.